2021
DOI: 10.22438/jeb/42/6/mrn-1798
|View full text |Cite
|
Sign up to set email alerts
|

Variability and genetic diversity study based on agro-morphological traits in a diverse set of Indian mustard [Brassica juncea (L.) Czern. & Coss.] germplasm

Abstract: Aim: The present investigation was designed to evaluate 150 diverse germplasm of Indian mustard along with five checks for seed yield and attributing traits. Methodology: A total of 150 genotypes of Indian mustard were evaluated in Augmented Block Design along with five check cultivars (Kranti, Maya, Pusa Bold, NPJ-112, RGN 73) in five blocks. Data were collected for 16 different quantitative traits on each genotype. Results: ANOVA revealed significant differences between genotypes for all traits studied. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Clustering of genotypes was irrespective of their geographical origin and no definite correlation was observed between genetic and geographical diversity. The present findings are in agreement with Saroj et al (2021), Sharma et al (2021), Devi et al (2017), Gupta et al (2015), Pandey et al (2013), Singh et al (2013), Dar et al (2010) and Doddabhimappa et al (2010). Further diverse origin may not always be used as an index for genetic diversity because divergence may also be due to genetic drift and selection pressure as concluded by Kole and Chakraborty (2012) and Murty and Arunachalam (1966).…”
Section: Resultssupporting
confidence: 93%
“…Clustering of genotypes was irrespective of their geographical origin and no definite correlation was observed between genetic and geographical diversity. The present findings are in agreement with Saroj et al (2021), Sharma et al (2021), Devi et al (2017), Gupta et al (2015), Pandey et al (2013), Singh et al (2013), Dar et al (2010) and Doddabhimappa et al (2010). Further diverse origin may not always be used as an index for genetic diversity because divergence may also be due to genetic drift and selection pressure as concluded by Kole and Chakraborty (2012) and Murty and Arunachalam (1966).…”
Section: Resultssupporting
confidence: 93%
“…It found useful identification traits in diverse genotypes of Indian mustard for different yield‐attributing traits (Sharma et al., 2021)…”
Section: Resultsmentioning
confidence: 99%
“…It found useful identification traits in diverse genotypes of Indian mustard for different yield-attributing traits (Sharma et al, 2021) 145 genotypes of Indian mustard were studied for terminal heat stress under late sown irrigated conditions. Preliminary findings shown effective use of discovered indices for selection of heat-tolerant lines in Indian mustard (Sharma et al, 2022) Mung bean (Vigna radiata) 2016-2018 It identified genotypes that may be utilized in improvement program of mung bean for rain-fed production (Kumar et al, 2020) Sweet sorghum (Sorghum bicolor)…”
Section: -2018mentioning
confidence: 99%
“…Therefore, parameters such as genotypic and phenotypic variance, heritability, and genetic advance are crucial for understanding the inheritance patterns of traits and determining their heritability. Understanding genetic correlations between traits aids breeders in optimizing selection efficiency by identifying favourable trait combinations and mitigating negative correlations (Sharma et al, 2021) [17] .…”
Section: Introductionmentioning
confidence: 99%